Addressing the viscosity challenge: ultrafast, stable-flow synthesis of zeolites with an emulsion method. Issue 6 (16th October 2018) - Zhu, Jie; Liu, Zhendong; Yonezawa, Yasuo; Honda, Kazuto; Okada, Satoshi; Deguchi, Shigeru; Okubo, Tatsuya; Wakihara, Toru
Abstract : Combined with a pipe-in-pipe system, the emulsion method can overcome the viscosity challenge, leading to the continuous flow synthesis of zeolites. Abstract : The sharp viscosity increase taking place in the zeolite formation renders continuous flow synthesis extremely challenging. We herein show that the emulsion system together with a Teflon-lined pipe reactor offers a unique opportunity to address the viscosity issue, allowing the zeolite products to smoothly flow out of the reactor in the form of a suspension. The emulsion-based, continuous flow synthesis of three important zeolites – ERI, *BEA and CHA – was achieved, demonstrating this method to be a general approach.